The Listening Comprehension Problem of Students at SDN 03 Bilah Barat Labuhan Batu - Wijaya, Indra; Purnawansyah Putra; Toni Megris; Deni Hardiansyah Harahap; Ahmad Sarif Rambe; M.Ali Hanafiah; Nora Mutiara Nazara; Slamet Triadi; Novysuryantiindrayani; Musliadi Sitompul; Sari Nasution (International Journal of Educational Research Excellence (IJERE), 2025)
Studying listening at SD 03 Bilah Barat Labuhan Batu has certain characteristics related to novices' majors. indonesian plays an essential role to be mastered by students. The orientation of students after graduating from school commonly gets a job related to their competency. Listening to a conversation, communicating, or tale in is an interest that desires to recognize the content material. Consequently, several aspects should be considered. This study investigated the main problems of listening comprehension in indonesia faced by vocational high school students. The findings show that the foremost troubles with information spoken text are unusual accents and subjects